Effects of Dopamine Receptor Activation on Synovial Fibroblasts Obtained from Rheumatoid Arthritis and Osteoarthritis Patients - van Nie, Lina; Justus Liebig University Giessen (My University, 2024)
Rheumatoid Arthritis is a chronic autoimmune disease, with inflammation of the joints and several extraarticular manifestations. Even though 1% of the world’s population is affected and a majority of patients is in working-age, there is still no cure for this disease. Chronic inflammation of the small joint of hands and feet are typical manifestations, which leads to hyperproliferation of the inflamed synovium. Synovial fibroblasts transfom into aggressive cells, that invade into adjacent bone and cartilage structures, leading to progressive damage of the joint. Furthermore, they secrete immunomodulatory factors and show uninhibited proliferation. In recent studies, dopamine has been shown to be synthesized in RASF, and all DR subtypes have been found on RASF. Compared to OA, dopamine receptors were overexpressed, pointing towards a significant role of DR in RA. For the first time we could show, that D1DR, D2DR, D3DR and D5DR are present in the invasion zone. Here, D1DR, D2DR and D5DR were stronger expressed in the invasion zone compared to the sublining layer. This suggests a distinct contribution of the dopaminergic system concerning invasion of RASF into cartilage and bone. All tested DR were also stronger expressed in the lining layer compared to the sublining layer in RA and OA synovium and all tested DR were stronger expressed in RA than in OA synovium. In contrast to previous publications, we could not find relevant alterations in IL6, proMMP1 and MMP3 release under specific D1-like and D2-like receptor activation in different concentrations. Here, the incubation time of 24h might have been too short, or optimized drug treatment prior to surgery might also lead to the observed reduced effects. Cell migration and also motility under specific D1-like and D2-like receptor activation was highly age-dependent on both RA and OA patients. Younger patients (<75 years) showed a significant increase of cell migration and motility, whereas older patients (>75 years) showed a significant decrease of migration an motility after D1-like and D2-like receptor activation, both in different concentrations and compared to the respective unstimulated control. Although effects were very similar between RASF and OASF, effects were stronger in RASF. In this study we further investigated the dopamine system in RASF and showed, that dopamine has significant age-dependent effects on cell migration and motility, crucial character traits of RASF. As DR activation has opposite effects on cell migration and motility according to the patient’s age, the dopaminergic system in RA should be further investigated in order to enable adequate treatment.
Keywords: Rheumatology; Dopamine; Cell Migration; Age-dependent; immuno-aging; ddc:610